Analysis of Diagnostic Properties of Some Regular Sensor Networks - Zbigniew ZIELIŃSKI; Jan CHUDZIKIEWICZ (Communications of International Proceedings, 2021)
In the paper the method of composing logical structures of  the hypercube network is presented. The method allows to determine the cardinality of labeled and unlabeled cyclic and acyclic sets of structures along with the network degradation process. The essence of the proposed method is the use of algebraic operations on so called condensed form of a structure. The number of coherent labeled (cyclic and acyclic) structures as well as coherent non-labeled (cyclic and acyclic) structures for the 4-dimensional hypercube processors network is given. The ability of working (degraded) structures of the hypercube network to faulty processors identifying under the comparison MM* model is defined and evaluated. The concept of degradation characteristics the hypercube processors network is introduced. The characteristics and distribution probability of the number of the 4-dimensional hypercube network processors faults after which it loses capability to function dependably are determined.
Keywords: Fault Tolerance; Hypercube Network; Diagnosability; Degradation Characteristics.